Sources of systematic bias in hypercapnia-calibrated functional MRI estimation of oxygen metabolism. - Chiarelli, P; Bulte, D; Piechnik, S; Jezzard, P (2007)
The change in cerebral rate of oxidative metabolism (CMR(O(2))) during neural activation may be estimated from blood oxygenation level-dependent (BOLD) functional magnetic resonance imaging (fMRI) and arterial spin-labeling (ASL) fMRI measurements. The established method relies on an epoch of iso-metabolic blood flow increase, typically induced by CO2 breathing, to calibrate the BOLD-CBF relationship at resting-state CMR(O2). Here, we discuss the systematic bias in CMR(O2)-CBF data that can be introduced depending on the value derived for the calibration constant (M) from the CO2 breathing epoch. We demonstrate that the fidelity of BOLD-CBF data acquired during the neural activation task have low impact on the tightness of CMR(O2)-CBF coupling, as well as the coupling slope, when the derived calibration value is of a relatively moderate amplitude (M in the range of, or greater than, 10-15 at 1.5 T). Via the standard reformulation of a grid in BOLD-CBF space into the CMR(O2)-CBF plane, we demonstrate the non-linear transformation that takes place and the sources of systematic bias that result. We find that the outcome of a neurovascular coupling study may be predicted to a large extent purely from the value of the calibration constant, M, that is used. Our results suggest that the accurate determination of M is of greater importance than thought previously and indicate that BOLD-CBF data must always be supplied when considering CMR(O2)-CBF behavior in a particular brain region.